Portable panel air conditioner - Mok, Khiaw Keat; Hassan, Mohd Fahrul; Ng, Chee Seng; Amir, Nurul Natasya; Ibrahim, Nor Syahira Syeri; Ahmad Maulana, Nur Shafikah (Penerbit UTHM, 2017)
CNC Computer Numerical Control machines as shown in Figure 5.1 are widely used in manufacturing industry. CNC Machining is a process used in the manufacturing sector which involve the use of computers to control machine tools. Tools that can be controlled in this manner include lathes, mills, routers and grinders. The CNC in CNC Machining stands for Computer Numerical Control. A CNC system consists of three basic components which are Part Program, Machine Control Unit (MCU) and Machine Tool.